Berry Phase, Berry Connection, and Chern Number for a Continuum Bianisotropic Material From a Classical Electromagnetics Perspective - Ali Hassani Gangaraj, S.; Silveirinha, Mario G.; Hanson, George W. (IEEE journal on multiscale and multiphysics computational techniques, 2017)
The properties that quantify photonic topological insulators (PTIs), Berry phase, Berry connection, and Chern number, are typically obtained by making analogies between classical Maxwell's equations and the quantum mechanical Schrödinger equation, writing both in Hamiltonian form. However, the aforementioned quantities are not necessarily quantum in nature, and for photonic systems they can be explained using only classical concepts. Here, we provide a derivation and description of PTI quantities using classical Maxwell's equations, demonstrate how an electromagnetic mode can acquire Berry phase, and discuss the ramifications of this effect. We consider several examples, including wave propagation in a biased plasma, and radiation by a rotating isotropic emitter. These concepts are discussed without invoking quantum mechanics and can be easily understood from an engineering electromagnetics perspective.